The (Un)ideal Physicist: How Humans Rely on Object Interaction for Friction Estimates - Karimpur, Harun; Wolf, Christian; Fiehler, Katja; Justus Liebig University Giessen (My University, 2024)
To estimate object properties such as mass or friction, our brain relies on visual information to efficiently compute approximations. The role of sensorimotor feedback, however, is not well understood. Here we tested healthy adults (N = 79) in an inclined-plane problem, that is, how much a plane can be tilted before an object starts to slide, and contrasted the interaction group with observation groups who accessed involved forces by watching objects being manipulated. We created objects of different masses and levels of friction and asked participants to estimate the critical tilt angle after pushing an object, lifting it, or both. Estimates correlated with applied forces and were biased toward object mass, with higher estimates for heavier objects. Our findings highlight that inferences about physical object properties are tightly linked to the human sensorimotor system and that humans integrate sensorimotor information even at the risk of nonveridical perceptual estimates.
Keywords: ddc:150